Chapter Market assessment and risk prediction: resources and know-how of a seventeenth-century bookseller of Venice coping with competition - ottone, andrea (Datini Studies in Economic History, 2023)
this article explores the likelihood that early modern printers had de-veloped rudimentary practices aimed at assessing their market of refer-ence to pursue strategic commercial planning. It surreys the inner evi-dence of a single manuscript bibliographic compiled by a minor mem-ber of the Giunta publishing house active in Venice in order to pro-pose the hypothesis that said catalogue may have been instrumental to commercial bibliometrics aimed to avoid harmful competition between redundant editions within the same market area.